2017
DOI: 10.1097/mat.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsatility on Microcirculation in Patients Treated with Extracorporeal Cardiopulmonary Resuscitation: A Pilot Study

Abstract: The effect of pulsatile blood flow on microcirculation during extracorporeal cardiopulmonary resuscitation (ECPR) is not elucidated; therefore, we designed an observational study comparing sublingual microcirculation in patients with refractory cardiac arrest (CA) with spontaneously pulsatile or low/nonpulsatile blood flow after treatment with ECPR. Microcirculation was assessed with Sidestream Dark Field technology in 12 patients with CA who were treated with ECPR and 12 healthy control subjects. Microcircula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This was documented by the results of a rat model study where cerebral cortical microcirculation recovered completely after ROSC and stayed preserved in the early post-resuscitation phase (up to 6 hours) though high inflammatory mediator levels and signs of neuronal death were present. 31-33…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This was documented by the results of a rat model study where cerebral cortical microcirculation recovered completely after ROSC and stayed preserved in the early post-resuscitation phase (up to 6 hours) though high inflammatory mediator levels and signs of neuronal death were present. 31-33…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent pilot study with 12 patients after refractory CA, who were treated with ECPR, suggested that ECLS might provide an adequate microcirculatory perfusion regardless of sustained or diminished spontaneous pulsatility. 32…”
Section: Literature Reviewmentioning
confidence: 99%